Glutamate Dehydrogenase Is Not Essential for Glutamate Formation by Corynebacterium glutamicum - Kholy, Elke R. Börmann-El (1993)
Two Corynebacterium glutamicum strains, one being glutamate dehydrogenase (GDH) negative and the other possessing 11-fold-higher specific GDH activity than the parental wild type, were constructed and used to analyze the role of GDH in C. glutamicum. The results indicate (i) that GDH is dispensable for glutamate synthesis required for growth and (ii) that although a high level of GDH increases the intracellular glutamate pool, the level of GDH has no influence on glutamate secretion.